2023
DOI: 10.1101/2023.01.30.525688
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human Abdominal Subcutaneous-Derived Active Beige Adipocytes CarryingFTOrs1421085 Obesity-Risk Alleles Exert Lower Thermogenic Capacity

Abstract: White adipocytes store lipids, have a large lipid droplet and few mitochondria. Brown and beige adipocytes, which produce heat, are characterized by high expression of uncoupling protein (UCP) 1, multilocular lipid droplets, and large amounts of mitochondria. The rs1421085 T-to-C single-nucleotide polymorphism (SNP) of the human FTO gene interrupts a conserved motif for ARID5B repressor, resulting in adipocyte type shift from beige to white. We obtained abdominal subcutaneous adipose tissue from donors carryin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…However, the exact nature of this temporal effect was not investigated. While more recent work by Vámos et al confirmed reduced thermogenic capacity in human adipose-derived precursor cells from patients homozygous for the FTO locus risk variants [35],…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, the exact nature of this temporal effect was not investigated. While more recent work by Vámos et al confirmed reduced thermogenic capacity in human adipose-derived precursor cells from patients homozygous for the FTO locus risk variants [35],…”
Section: Discussionmentioning
confidence: 96%
“…The present study has identified hundreds of novel direct target genes of the homeobox transcription factor Irx3 in preadipocytes, providing mechanistic insight into how IRX3 mediates the association between risk variants in the FTO locus and increased risk of obesity [12][34]. We previously found a transient, risk genotype-dependent increase in IRX3 during early adipogenesis to promote white over beige adipocyte identity of the mature adipocytes [12,35]. These data suggest an epigenetic effect of Irx3 and despite its lack of chromatin or histone-modifying domains we here found that chromatin remodeling and histone modifying enzymes were the top enriched biological pathways among the identified direct Irx3 target genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation